The way of the Indian : thirteen documentary programs broadcast on CBC radio. (CBC Publications, 1963)
This booklet contains an edited transcript of The Way of the Indian -- thirteen half-hour documentary programs broadcast on CBC radio during the summer and fall of 1961. The purpose of the documentary was to explore the lives of Canada's Aboriginal peoples.